Chinese Migration and Multicultural Transformation in Sirenja District, Central Sulawesi (1950–2000) - Revy Mariska; Lukman Nadjamuddin; Minarni Nongtji (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to analyze the existence, socio-economic roles, and migration factors of the Chinese ethnic community in Sirenja District, Donggala Regency, during the period 1950–2000. The research employed a qualitative approach using historical research methods, including heuristics, source criticism, interpretation, and historiography. Data were collected through in-depth interviews, field observations, and archival and local historical documentation. The findings reveal that the Chinese community played a significant role in local economic development through trading activities, goods distribution, and commercial relations with coastal communities. Social interaction between Chinese Indonesians and residents was relatively harmonious, supported by economic cooperation, social communication, and cultural adaptation. However, the Chinese community also maintained internal solidarity and kinship networks as part of their socio-economic survival strategy. The study further found that the migration of Chinese Indonesians from Sirenja during the late 1990s and early 2000s was influenced by declining local economic activity, changes in regional trade structures, and broader national socio-political conditions during the Reformasi era. This migration contributed to weakening commercial activity and reducing multicultural interaction within the district. This research contributes to the development of local historical studies, ethnic migration research, and discussions on multicultural societies in Indonesia, particularly concerning Chinese communities in the coastal areas of Central Sulawesi